HUBUNGAN ANTARA ASUPAN ENERGI, ASUPAN PROTEIN DAN TINGKAT DEPRESI DENGAN STATUS GIZI PASIEN GANGGUAN JIWA (Studi di Rumah Sakit Jiwa Propinsi Kalimantan Barat) - Mariati, Sri; Marlenywati, Marlenywati; Budiastutik, Indah (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Mental illnessis a set of physical and mental abnormal circumstances. Oneof which isdepression. A preliminary surveyconducted to 10patients atpsychiatric hospitalof West Kalimantan, by considering IMT,showed that patients withmalnutrition statuswere  20%, and patients with  normal nutritionalstatus were  80%. Data gathered by using Comstok method  indicated that 30% patients had less energyandproteinintake, and 70% patients had adequate energy and protein intake. In addition, data of DBI indicated that patients withseveredepression levelswere 40%and patients with moderatelevel ofdepressionwere 60%.This study aimed at discovering the correlation of energy intake, protein intake, depression level, and nutritional status of mental illness patients at psychiatric hospital of West Kalimantan, using cross sectional design, this study employed 615 inclusive criteria population.  As many as 148 samples were selected by using proportional random sampling. The data were statistically analyzed by using chi square test.The study revealed that there were correlation of nutritional status ( p value= 0,000, PR = 7,250), protein intake (p value = 0,000, PR = 5,143) and depression levels (p value = 0,000, PR = 9,046).The management of hospital need to enhance the quality and the menu modification in order to stimulate and increase the patients’ appetite. The menu modification is also important to reduce the patients’ boredom on the given menu and avoid them leaving the food on the plate. Key words     : energy intake, protein, depression levels,  nutritional status of mental illness patients